PENERAPAN SYSTEM VENDOR MANAGE INVENTORY TERHADAP PENGHEMATAN BIAYA KETERSEDIAAN BAHAN BAKU DAN LOGISTIK DI PT.PRASINDA NUGRAHA - Jurnal Ilmiah Manajemen Universitas Putera Batam (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
The focus in this research is to find out whether the implementation of VMI system can be reduced logistics cost and raw material cost at PT. Prasinda Nugraha. This research is an alleged operational cost and target sales target caused by the decline. The sample has been taken from PT.Prasinda Nugraha financial report period 2014 - 2017 so that the sample. The data that has been taken is done to measure and ensure that the data already exists under normal circumstances and feasible for further analysis. The result of this research is significant influence (58,7%) between applying VMI system (Vendor Manage Inventory) to decreasing logistic cost (Y1). This study also proves a significant influence (73.2%) of the application of VMI to the decline in the cost of providing raw materials to increase product sales in PT. Prasinda Nugraha.